Descartes and method : a search for a method in Meditations - Flage, Daniel E., 1951- (Routledge studies in seventeenth-century philosophy, 1999)
In this genuinely ground-breaking book the authors argue against the orthodox conception that Descartes had no method. Through a rigorous and thorough examination they unearth and explain the role of the method of analysis in Meditiations.